Increase in the influenza vaccination rates in Portugal: comparing 2020-2021 to the last 10 years. (20th October 2021) - Guedes, L; Figueiredo, AL; Afonso, AL; Couto, ML; Natividade, A; Gouveia, AJ; Saldanha, MG; Sousa, MF; Oliveira, P; Martinho, C
Abstract: Background: Annual influenza vaccine uptake is recommended by the Portuguese General-Directorate of Health to certain priority groups. In 2020, amidst the COVID-19 pandemic, some exceptional measures were adopted to operationalize the Portuguese influenza vaccination campaign, like the extension and phasing of the vaccination period. No major changes were introduced in the vaccination of healthcare workers. In Baixo Tâmega health cluster (Portugal), it was perceived that these workers' vaccine uptake had markedly increased in 2020-2021. This study aims to compare their influenza vaccination coverage rates in 2020-2021 to the last 10 seasons. Methods: A cross-sectional study of the vaccine uptake among the health workers of Baixo Tâmega health cluster was developed. A descriptive analysis was carried out, calculating annual influenza vaccination coverage rates from 2010-2011 to 2020-2021, in doctors, nurses and other health workers. Inferential analysis was performed through chi-squared tests in IBM SPSS Statistics 27.0.1.0., considering significant p-values<0.05. Results: The difference between health workers 2020-2021's influenza coverage rate and the last season's average rates was 22.81%. Before 2020-2021, average vaccination coverage rates were 51.60% (standard deviation 7.34%, 44.26-58.94%), 60.44% (standard deviation 4.12%, 56.32-64.56%) and 51.20% (standard deviation 7.66%, 43.54-58.86%), in doctors, nurses and other health workers, respectively. In 2020-2021, vaccination rates significantly increased to 79.34%, 79.52% and 74.24% in doctors, nurses and others, respectively (p < 0.001). Conclusions: Influenza vaccination uptake increased in 2020-2021 among health workers. Further studies should be developed to evaluate this tendency on a larger scale and to better understand its associated factors, which could have been unstructured awareness-raising campaigns, perception of protection against COVID-19 or avoidance of COVID-19-like symptoms and coinfection. Key messages: Influenza vaccination coverage rates increased in 2020-2021 among the healthcare workers of a Portuguese health cluster. The COVID-19 pandemic may have contributed to the increase in the influenza vaccination coverage rates.